ANALISIS YURIDIS TERHADAP PENGANGKATAN KEMBALI NOTARIS YANG TELAH DINYATAKAN PAILIT OLEH PENGADILAN - Putri Pertiwi Santoso (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract According to article 12 paragraph a of Law Number 2 Year 2014 concerning the Amendment to Law Number 30 Year 2004 concerning Notary, notaries can be fired because it has been declared bankrupt by a court decision that has obtained permanent legal force. Dishonorable dismissal is a treatment that is not in accordance with the concept of bankruptcy because the bankruptcy law itself regulates legal efforts to protect the interests of creditors provided for in Article 24 paragraph 1 of Law No. 37 Year 2004 on Bankruptcy and Suspension of Payment. Bankruptcy is applicable to legal entities and also to individuals. So that a conflict arises between the law concerning the legal consequences of bankruptcy experienced by a notary. This thesis discusses about. Are the provisions in Article 12 letters a Notary Act is not contrary to law number 37 of 2004 on bankruptcy related to the inadequacy someone who had been cut off bankruptcy and notary Can be reappointed after completing the bankruptcy process. The purpose of this journal is to know and analyze whether the provisions in article 12 paragraph a Notary Act is not contrary to law number 37 of 2004 on bankruptcy related to the inadequacy someone who has terminated bankruptcy, and to identify and analyze the notary can be reappointed after completing the bankruptcy process. This journal using the Theory of Rule of Law and Theory of Justice. This journal is a study using the approach Normative Legislation and Conceptual Approach. Results of this journal is that the contradiction between the Law Notary with the Bankruptcy Act, namely the legal consequences experienced by a notary who has been sentenced for bankruptcy, and the existence of a legal vacuum regarding the reappointment of the notary who has completed the bankruptcy process. Key words: bankruptcy, appointment return, legal due notaries, notary termination Abstrak Menurut pasal 12 huruf a Undang-undang Jabatan Notaris, notaris dapat diberhentikan secara tidak hormat karena telah dinyatakan pailit berdasarkan putusan pengadilan yang telah memperoleh kekuatan hukum tetap. Pemberhentian secara tidak hormat ini merupakan perlakuan yang kurang sesuai dengan konsep kepailitan karena hukum kepailitan itu sendiri mengatur tentang upaya hukum untuk melindungi kepentingan kreditur yang diatur di dalam pasal 24 ayat 1 Undang-undang Tentang Kepailitan. Sehinga timbul pertentangan antara kedua Undang-undang tersebut mengenai akibat hukum dari kepailitan yang dialami notaris. Jurnal ini membahas mengenai. Apakah ketentuan di dalam pasal 12 huruf a Undang-undang Jabatan Notaris tidak bertentangan dengan Undang-undang nomor 37 tahun 2004 tentang kepailitan terkait dengan ketidakcakapan seseorang yang telah diputus pailit dan Dapatkah notaris diangkat kembali setelah menyelesaikan proses pailit. Tujuan jurnal ini adalah Untuk mengetahui apakah ketentuan di dalam pasal 12 huruf a Undang-undang Jabatan Notaris tidak bertentangan dengan Undang-undang nomor 37 tahun 2004 tentang kepailitan terkait dengan ketidakcakapan seseorang yang telah diputus pailit, dan untuk mengetahui dan dapatkah notaris diangkat kembali setelah menyelesaikan proses pailit. Jurnal ini menggunakan Teori Kepastian Hukum dan Teori Keadilan. Jurnal ini merupakan penelitian Normatif dengan menggunakan Pendekatan Perundang-Undangan dan Pendekatan Konseptual. Hasil dari penulisan jurnal ini adalah bahwa adanya pertentangan antara Undang-Undang Jabatan Notaris dengan Undang-Undang Kepailitan yaitu mengenai akibat hukum yang dialami oleh notaris yang telah dijatuhi pailit, dan adanya kekosongan hukum mengenai pengangkatan kembali terhadap notaris yang telah menyelesaikan proses pailit. Kata kunci: kepailitan, pengangkatan kembali, akibat hukum notaris, pemberhentian notaris